IMPLEMENTASI PERATURAN WALIKOTA NOMOR 138 TAHUN 2020 TENTANG PENYELENGGARAAN PERPARKIRAN DI KOTA PEKANBARU TAHUN 2024 - Putra, Winndy Masyka; Nasution, Hazqon Fuadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The rapid growth of Pekanbaru City has led to illegal parking problems that have an impact on the smooth flow of traffic, security, and city order. Although the Transportation Agency through UPT Perparkiran has conducted patrols and enforcement, parking violations still occur frequently. The main problem lies in the lack of public awareness, weak policy socialization, limited human resources, and not optimal supervision. This research aims to analyze the implementation of Mayor Regulation Number 138 of 2020 concerning the Implementation of Parking in Pekanbaru City, especially on the implementation on Jalan HR. Soebrantas, and identify inhibiting factors in its implementation. This research uses the theory of public policy implementation by referring to the George C. Edwards III model, which highlights four main variables: communication, resources, disposition (executor attitude), and bureaucratic structure. The success of policy implementation is strongly influenced by clarity of communication, adequacy of resources, commitment of implementers, and a supportive organizational structure. The research method used is descriptive qualitative. Data were collected through interviews, observations, and documentation of informants from the Transportation Agency, UPT Perparkiran, parking officers, and the public who use parking services on Jalan HR. Soebrantas. Data analysis was carried out by reducing, presenting, and drawing conclusions from the data obtained. The results showed that the implementation of Mayor Regulation Number 138 of 2020 still faces various obstacles. Communication and socialization of policies are not optimal so that people do not understand parking rules. Human resources, both in terms of number and competence of officers, are still limited. Supervision of parking implementation is also not optimal, so illegal parking violations still occur frequently. Increased socialization, officer training, and stricter supervision are needed so that the parking system in Pekanbaru City can run effectively and accountably. Keywords: Implementation, Monitoring, Parking, Illegal parking